Florbetapir F18 PET Amyloid Neuroimaging and Characteristics in Patients With Mild and Moderate Alzheimer Dementia - Degenhardt, Elisabeth K.; Witte, Michael M.; Case, Michael G.; Yu, Peng; Henley, David B.; Hochstetler, Helen M.; D’Souza, Deborah N.; Trzepacz, Paula T. (Psychosomatics (Washington, D.C.), 2016)
Clinical diagnosis of Alzheimer disease (AD) is challenging, with a 70.9%–87.3% sensitivity and 44.3%–70.8% specificity, compared with autopsy diagnosis. Florbetapir F18 positron emission tomography (FBP-PET) estimates beta-amyloid plaque density antemortem. Of 2052 patients (≥55 years old) clinically diagnosed with mild or moderate AD dementia from 2 solanezumab clinical trials, 390 opted to participate in a FBP-PET study addendum. We analyzed baseline prerandomization characteristics. A total of 22.4% had negative FBP-PET scans, whereas 72.5% of mild and 86.9% of moderate AD patients had positive results. No baseline clinical variable reliably differentiated negative from positive FBP-PET scan groups. These data confirm the challenges of correctly diagnosing AD without using biomarkers. FBP-PET can aid AD dementia differential diagnosis by detecting amyloid pathology antemortem, even when the diagnosis of AD is made by expert clinicians.